Речные раки (Crustacea, Astacidae) Советского Союза. Сообщение II. Распространение длиннопалого рака — Astacus (Pontastacus) leptodactylus Eschscholts, 1823 - Бродский, С.Я. (Вестник зоологии, 1974)
A study of taxonomy and peculiarities in distribution of the most frequent genus Astacus (Pontastacus) leptodactylus Eschscholtz, 1823 and its smaller taxons as well as an analysis of the literature data testify to the fact that in nature the areas of distribution with one species of Astacidae are very rare; very often even one water body is inhabited by some taxons. The character of the Astacidae taxons distribution is significant for comprehension and estimation of origin of crawfishes and their modern distribution as well as for rational utilization and protection of their reserves, for acclimatiza- tion and cultivation.